Does agricultural commercialisation increase asset and livestock accumulation on smallholder farms in Ethiopia? - Tabe-Ojong, Martin Paul Jr.; Hauser, Michael; Mausch, Kai (Informa UK Limited, 2022)
The transition of farmers from subsistence to market-oriented agriculture is meant to reduce hunger, increase wellbeing and accelerate rural economic progress. While an impressive extant literature has analysed agricultural commercialisation effects on welfare from an income, expenditure and consumption perspective, authors place less attention on the implications on asset holdings, which is a more robust long-term measure of welfare. Using chickpea production in Ethiopia as a case, we assess the effects of chickpea commercialisation on household asset ownership and livestock holdings of smallholder farmers. We employ a household fixed-effects estimator to control for time-invariant unobserved heterogeneity and account for possible endogeneity using an instrumental variable approach. For comparison purposes, we also evaluate the income effects of chickpea and examine impact heterogeneity using quantile regressions. Our results indicate a positive impact of agricultural commercialisation on assets, livestock ownership and income. We found commercialisation to benefit all farmers in terms of impact heterogeneity, though with higher gains for asset-rich households. Despite this rising asset inequality, we conclude that increased agricultural commercialisation can contribute to economic development of households and reduce rural poverty.